2017
DOI: 10.3390/ma10090997
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the Ignition, Hardness and Compressive Response of Magnesium by Reinforcing with Hollow Glass Microballoons

Abstract: Magnesium (Mg)/glass microballoons (GMB) metal matrix syntactic foams (1.47–1.67 g/cc) were synthesized using a disintegrated melt deposition (DMD) processing route. Such syntactic foams are of great interest to the scientific community as potential candidate materials for the ever-changing demands in automotive, aerospace, and marine sectors. The synthesized composites were evaluated for their microstructural, thermal, and compressive properties. Results showed that microhardness and the dimensional stability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
29
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
3

Relationship

4
6

Authors

Journals

citations
Cited by 51 publications
(33 citation statements)
references
References 49 publications
4
29
0
Order By: Relevance
“…It can be inferred that that the addition of Sm 2 O 3 NPs helped in increasing the insulating property of pure Mg [33]. Further, the thermal conductivity of the composites is directly related to the amount of reinforcement added to the matrix, and in view of the ability of reinforcement to reduce the availability of metallic matrix for ignition, also leads to increased ignition performance with progressive addition of Sm 2 O 3 NPs [34].…”
Section: Ignition Propertiesmentioning
confidence: 95%
“…It can be inferred that that the addition of Sm 2 O 3 NPs helped in increasing the insulating property of pure Mg [33]. Further, the thermal conductivity of the composites is directly related to the amount of reinforcement added to the matrix, and in view of the ability of reinforcement to reduce the availability of metallic matrix for ignition, also leads to increased ignition performance with progressive addition of Sm 2 O 3 NPs [34].…”
Section: Ignition Propertiesmentioning
confidence: 95%
“…In the recent past, Mg-based materials for their advantageous properties for medical applications such as biodegradable capacity, good cytocompatibility, favorable mechanical properties, and elastic modulus closer to load bearing bones, unique antibacterial and osteo-promotive properties, have emerged as a new class of biomaterials for orthopedic applications such as implants and fixation devices [61,62]. Mg-based implants share a similar specific density to that of human bone (Table 1), unlike commonly used permanent biomaterials such as stainless steels and titanium alloys [62,63]. Further, in comparison to commercially used orthopedic implants like titanium alloys, stainless steel, and cobalt-chromium (Co-Cr) alloys, Mg possesses considerably lower elastic modulus matching the elastic modulus of the bone (trabecular/cancellous bones) which aids in eliminating/decreasing any possible stress shielding effects at the bone/implant interface and facilitate new bone formation [64][65][66][67].…”
Section: Magnesium/magnesium Alloysmentioning
confidence: 99%
“…In the recent times, the lightweight materials research community's emphasis has been to examine the effect of nano-sized reinforcement particle addition on the thermal and mechanical behavior of aluminum composites [10,13,14]. Also, metallic glasses as reinforcing phases have garnered considerable attention owing to their high hardness, mechanical strength, enhanced corrosion resistance, and good functionality [15][16][17]. Several researchers have reported that uniformly distributed metallic glass reinforcement nanoparticles have the ability to simultaneously improve the strength and ductility of AMMCs [2,[18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%